A Correlational Study Between Students’ Learning Motivation, Vocabulary Mastery And Pronunciation - Fakhrurrazi M. Amin (CV. Eureka Murakabi Abadi, 2023)
The aim of this research is to find out whether there is significant correlation between the students’ learning motivation, vocabulary mastery and pronunciation skill at SMPN 5 Langsa. The method of this research is quantitative with correlational design. The research object of this research is 55 students. The data were collected by applying test and questionnaire. Indeed, based on the result of the research, it showed that there is a positive correlation between students’ learning motivation and pronunciation skill at SMPN 5 Langsa, there is a positive correlation between students’ vocabulary mastery and pronunciation skill, and there is a positive correlation between students’ learning motivation, vocabulary mastery and pronunciation skill. It can be concluded that students’ learning motivation gives contribution to both their vocabulary mastery and their pronunciation skill. Additionally, when students have high motivation in learning, it can be beneficial to them in order to improve their vocabulary mastery and their pronunciation skill.